Covid-19 Pandemic Disaster Mitigation Training as an Effort to Minimize the Spread of Coronavirus in Majalaya Sub-District, Bandung Regency, Indonesia - Sukono Sukono; Endang Soeryana Hasbullah; Yuyun Hidayat (International Journal of Research in Community Services, 2021)
The Covid-19 pandemic has hit almost all countries in the world, including Indonesia. In addition, the COVID-19 pandemic has also affected the education system in Indonesia, which causes the learning system to be conducted online. However, in some regions in Indonesia, it is allowed to organize a face-to-face learning system. Where according to the direction of the Minister of Education and Culture in the 2021/2022 school year, it will be held with limited face-to-face learning while still implementing health protocols. Through the Community Service program with the topic "Covid-19 Pandemic Disaster Mitigation Training as an Effort to Minimize the Spread of Coronavirus in Majalaya District" aims to increase motivation to learn during a pandemic and provide understanding to students (i) SMA Negeri 1 Majalaya regarding the impact of the Covid-19 Pandemic and health protocols that have been set by the Ministry of Health in an effort to minimize the spread of the coronavirus. This activity is intended for students (i) SMA Negeri 1 Majalaya by using the direct presentation method. This activity began with giving questionnaires to students to determine the level of student learning motivation during the Covid-19 pandemic. The results of the questionnaire showed that during the Covid-19 pandemic, students' learning motivation was quite affected. In addition, after counseling about the Covid-19 Pandemic disaster mitigation using Power Point media and games, there was an increase in knowledge of the impact of the Covid-19 Pandemic and the health protocols set by the Ministry of Health in an effort to minimize the spread of the coronavirus. Based on the results in the field, this activity has proven successful in increasing the knowledge of SMP Negeri 1 Majalaya regarding the mitigation of the Covid-19 Pandemic.